Can land prices be used to curb urban industrial land expansion? An explanation from the perspective of substitutability of land in production. Issue 4 (2nd October 2022) - Zhao, Aidong; Huang, Jinsheng; Ploegmakers, Huub; Lan, Jing; van der Krabben, Erwin; Ma, Xianlei
Abstract: Industrial land expansion has become a matter of increasing concern to policy-makers, especially in developing and emerging manufacturing countries. Price mechanisms are regarded as an important way to control the expansion of industrial land. For industrial land, the effectiveness of a price mechanism in controlling land expansion relies substantially on the substitutability of land in production, which remains unclear in the literature. This paper provides empirical evidence on the substitutability of industrial land by examining the impact of increases in land prices on the elasticity of substitution between land input and other production factors based on China's city-level industrial production in 2007–2015. We find that land price increases significantly induce the industrial sector to reduce land demand by substituting capital for land. However, our estimated elasticity of substitution of capital for land in production is only 0.03, which indicates that industrial land is substitutable but the degree of substitutability is very low in production. The findings of our study suggest that the benefits of relying on price mechanisms to curb industrial land expansion may be very limited; hence, traditional planning instruments should also be suitably designed to jointly curb industrial land expansion.